INVESTIGATING THE RELATIONSHIP BETWEEN SELF-ESTEEM AND NARCISSISM LEVEL OF FEMALE BADMINTON PLAYERS - Ünsal TAZEGÜL (Fırat University, 2019)
When the narcissistic personality is analysed at literature, it is seen that it is described as person’s over favor and admire to himself to his own physical and physicological features. But self-respect is described as person’s feeling of himself as valued, active, proud, studious and successful. The aim of this study is to demonstrate the relationship between Female Badminton Players ' self-esteem and narcissism level by determining their narcissism and self-esteem. Narciccism personality scale and self-esteem scale are used for gathering data in this study. In the analysis of the data, SPSS 15 program was used. “Kolmogorov-Smirnov” and ''Anova-Homogenety of variances” tests were applied in order to determine if the data are normally distributed. The tests results indicated that the data are normally distributed and homogeny. Descriptive statistic test for analysing the data and Pearson correlation tests for examining the relationship between narcissism and self-esteem are used in the study. At the end of the study, a positive relationship between narcissism and self-esteem are determined. At the end of many research that have been done for self-respect, It has been detected that the self-respect of the peoples who have attented in sportive activities are more developed than the self-respect of the people who have not attended in sportive activities. Sport not only make a positive contribution to the self-respect of the person but also plays an important role for decreasing the stres, anxiety, which affect negatively to the mental health of the person and for the personality development, too.